CLASSIFICATION AND AVERAGE CHEMICAL COMPOSITIONS OF COMMON BASALTS AND ANDESITES - Wilkinson J.F.G. (My University, 1986)
A chemical classification of common basalts and andesites is proposed which utilizes CIPW normative plagioclase compositions (100 an/(ab + an) = AN), differing levels of silica saturation (with respect to CIPW qz, hy, ol or ne), and whole rock Al2O3 abundances and K2O/Na2O ratios (weight per cent). Extrusives belonging to the basalt-andesite spectrum are divided into subalkaline (tholeiitic or calc-alkaline; qz > 0) or alkaline (ne > 0) types. If qz + ne = 0 hy-normative volcanics are designated subalkaline or transitional (mildly alkaline) after applying the discrirninant of Chayes (1966). The division between basalt sensu lato and andesite s.l. is taken at normative plagioclase AN 50 and the lower limit for andesite s.l. is set at AN 30. 100 Mg/(Mg+Fe2+) ratios (M)(M > 75, AN > 50) from basalts (M ⋜75, AN > 50). A division at 16 per cent Al2O3 delineates low-Al ( ⋜16 per cent Al2O3 and high-Al (> 16 per cent Al2O3 basaltic and andesitic sub-types which collectively can span the range of CIPW silica saturation levels. Volcanics with K2O/Na2O ratios less than 0.5 are prefixed by the qualifier ‘low K/Na’, those with K2O/Na2O ratios between 0-5 and 10 by ‘medium K/Na’ and those with K2O/Na2O ratios greater than 1.0 are termed ‘high K/Na’. An additional group of low-K tholeiitic extrusives (MORB-type) is distinguished by very low K2O abundances (K2O ⋜0.3 per cent). Average chemical compositions of the various volcanic species are based on analyses retrieved from the CLAIR-PETROS data base. Each average employs only analyses whose parameters conform with those defining that species in the classification. Analyses with more than 2 per cent H2 or with molar 2Fe2/FeO greater than 1.0 were rejected during analysis retrieval. Many of the new averages agree closely with other average chemical compositions based on analyses selected via the rock nouns originally assigned to them. The classification employs only 6 root names (andesite, basalt, basanite, dacite, picrite, tholeiite). It attempts to provide an integrated classification of common basalts and andesites whereby the same values for critical normative and other parameters (AN, qz or ne, Al2O3 contents and K2O/Na2O ratios) are applied to all basalts and andesites irrespective of magmatic affinities. The proposed classification makes no provision for basaltic andesite, trachybasalt, trachyandesite and shoshonite, mainly because of inconsistent usage over the years and/or initially imprecise definitions.